The construction of characters with disabilities in film: The importance of verbal and non-verbal communication - Sanz-Simón, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Since the beginnings of cinema, stereotypes have been used to represent disability. It generates an inadequate image of the condition. The aim of this research is to analyse the verbal and non-verbal communication of eight characters in order to check whether they contribute to verifying the existence or absence of stereotypes. To this end, discourse analysis and content analysis have been used. The results, based on the interpretation of the meaning of the characters' signs, allow us to conclude that communication processes are essential for their classification.